LAY PARTICIPATION IN THE ADMINISTRATION OF JUSTICE: INTERNATIONAL EXPERIENCE AND PRACTICE - X. Z. Kudratillaev (Ecominds Press, 2026)
The involvement of lay representatives in judicial proceedings represents a fundamental principle of democratic justice systems worldwide. This article examines the comparative experience of jury systems, lay assessors, and mixed tribunals across different legal traditions, analyzing their implementation in common law, continental European, and post-Soviet jurisdictions. Particular attention is devoted to the legislative framework and practical application of lay participation in the Republic of Uzbekistan, contextualizing it within broader international trends and best practices. The analysis demonstrates that while Uzbekistan's legal framework formally provides for citizen participation through lay assessors, practical implementation faces significant challenges including low utilization rates, limited training infrastructure, and insufficient public awareness. Drawing on successful European models, particularly Germany's Schöffen system, this study identifies concrete recommendations for strengthening lay participation as a mechanism for enhancing democratic legitimacy and procedural fairness in Uzbekistan's evolving justice system
Keywords: Lay participation, jury system, lay assessors, judicial reform, comparative law, Uzbekistan, democratic legitimacy, criminal procedure.